STRATEGI PENGEMBANGKAN USAHA PADA UMKM DI ERA NEW NORMAL PANDEMI COVID-19 (Studi Kasus Pada UMKM Bolen Lumer Yulia di Demak): Manajemen - Sulistyorini Sulistyorini; Masine Slahanti (Pusat Riset dan Inovasi Nasional, 2021)
ABSTRAK. The purpose of this research is to find out the right strategy in business development and knowing the strengths, weaknesses, opportunities and threats in Yulia's melted cake business during the current New Normal situation. The research was conducted on Yulia's melted ballen cake UMKM in Demak. Methods of data collection is done by observation and interviews. The results of the study show that the strategy used in business development is through management strategy namely the process of planning, organizing, directing, supervising the business carried out by UMKM, so that the product, price, taste and location of the business make a business become developed which previously was in the house now has a shop by the side of the road, Then investment strategies such as personal capital, loans from banks, equipment, vehicles, shop houses owned by , Bolen Lumer Yulia, make the business grow, with a business strategy that maintains product quality, quality of human resources, promotions, cooperation, expanding capital will affect the business development undertaken by UMKM, cakes bolen lumer yulia. However, the development strategy that will be implemented must be in accordance with the external and internal environment, so in a competitive strategy an analysis of external and internal factors is needed through a SWOT analysis, namely by looking at the strengths and weaknesses as well as threats and opportunities.